Dual-Functional 2D/2D Inhibitor-Loaded ZnAl-LDH/Graphene Oxide Nanohybrid for Active/Passive Integrated Corrosion Protection in Waterborne Epoxy Coatings - Zhang, Hongyi (Langmuir : the ACS journal of surfaces and colloids, 2025)
The long-term anticorrosion ability of graphene oxide-based waterborne epoxy composite coating is greatly restricted due to easy aggregation, high conductivity, and limited functionality. Herein, a multifunctional 2D/2D hybridized nanofiller, graphene oxide/ZnAl-LDH loaded with 2-aminomalonamide (LDHAMA-MrGO), was constructed by synthesizing ZnAl-LDH loaded with 2-aminomalonamide (AMA) via a hydrothermal route and assembling it onto the surface of melamine-functionalized graphene oxide via electrostatic attraction. The obtained multifunctional LDHAMA-MrGO hybridized nanofiller was added to waterborne epoxy coatings, and their anticorrosion performance was measured by electrochemical impedance spectroscopy (EIS) testing. With the addition of 1.5 wt % LDHAMA-MrGO hybridized nanofiller, the low-frequency impedance modulus |Z|0.01 Hz of the WEP composite coating, after immersion in 3.5 wt % NaCl medium for 100 days, remained 3.05 × 109 Ω·cm2, which was 3 orders of magnitude higher than that of the neat WEP coating. The results of salt spray testing and scanning electrochemical microscopy (SECM) confirmed that the synergistic labyrinth effect of 2D/2D LDH/GO layered nanosheets and the formation of a passivation film contributed to the improvement of the long-term corrosion resistance of WEP composite coatings. Density functional theory (DFT) and molecular dynamics (MD) simulations based on quantum computing elucidated the diffusion mechanism of corrosive media and the coordination interaction between metals and corrosion inhibitors. In addition, the enhanced mechanical properties, including impact resistance, adhesion, and friction resistance, strongly supported the long-term use of WEP coatings, showing broad application prospects in metal protection in complex corrosive environments